Genetically Predicted Atrial Fibrillation and Valvular Heart Disease: A Two-Sample Mendelian Randomization Study - Gao, Jie; Bai, Yulin; Ji, Hongwen (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have found atrial fibrillation (AF) is associated with valvular heart disease (VHD). However, whether there is a causal relationship between these two diseases or it is just a result of bias caused by confounding factors is uncertain. This study aims to examine the potential causal association between AF and VHD by using Mendelian randomization. Methods: In order to examine the causal relationship between AF and VHD, we performed a two-sample mendelian randomization study by collecting exposure and outcome data from genome-wide association study (GWAS) datasets. We utilized data from FinnGen project (FinnGen, 11258 cases for VHD including rheumatic fever, 3108 cases for non-rheumatic VHD and 75137 cases for participants) and European Bio-informatics Institute database (EBI, 55114 cases for AF and 482295 cases for participants). Inverse-variance weighted (IVW), MR-Egger, and weighted median approaches were performed to estimate the causal effect. Results: The Mendelian randomization analysis indicated that AF increased the risk of VHD by all three MR methods ( For VHD including rheumatic fever: IVW, odds ratio [OR]=1.255; 95% confidence interval [CI], 1.191～1.322; p=1.23×10-17; Weighted median, OR=1.305, 95% CI, 1.216～1.400, p=1.57×10-13; MR-Egger, OR=1.250, 95% CI, 1.137～1.375, p=1.69×10-5; For non-rheumatic VHD: IVW, OR=1.267; 95% CI, 1.169～1.372; p=6.73×10-9; Weighted median, OR=1.400; 95% CI, 1.232～1.591; p=2.40×10-7; MR-Egger, OR=1.308; 95% CI, 1.131～1.513; p=5.34×10-4). After the 1 outlier SNP was removed by heterogeneity test, the results remained the same. No horizontal pleiotropic effects observed between AF and VHD. Conclusions: Our study provides strong evidence of a causal relationship between AF and VHD. Early intervention for AF patients may reduce the risk of developing into VHD.